Aural Laureate [Scott Jones biography]. - Karlin, S.
In this paper, the author presents a biography of entrepreneur Scott Jones, describes how Jones built a better voicemail system and how he now hopes to do the same for home entertainment.
Keywords: Scott Jones; Biography; Entrepreneur; Home entertainment; Voicemail system